Sonogram features of myxomatous mitral valve disease and abdominal organ dissorders in a senior mini pomeranian - Nindya Dwi Utami; Deni Noviana (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
A 12-years-old mini pomeranian with clinical symptom of coughing was referred to Veterinary Teaching Hospital, Faculty of Veterinary Medicine, Bogor Agricultural University for evaluation. The radiogram showed difus interstitial nodular pattern on the lungs and enlargement of the spleen. Abdominal ultrasonography and echocardiography was performed to further diagnose the dog. Abdominal ultrasonography was taken using linear probe with frequency 5-11 MHz. Echocardiography was perfomed with right parasternal and left apical views using microconvex probe, with frequency 6-8.8 MHz. Abdominal utrasonogram showed that the dog had billiary sludge, mild splenitis, nephrolithiasis, and urolithiasis. Two dimensional Brightness-mode echocardiography showed thickened and prolapsed mitral valve. Two-dimensional M-mode echocardiography showed increasing of left ventricle lumen dimension (LVID) at systole, decreasing of fractional shortening (FS), and enlargement of left atrial. Color Flow Doppler-mode revealed there was mild regurgitation at the mitral valve. These results lead diagnosis to dilated cardiomyopathy and myxomatous mitral valve disease